Efektivitas Teknik Ecola (Extending Concept Through Language Activities) terhadap Pembelajaran Membaca Pemahaman Teks Berita pada Siswa Kelas VIII SMPN 1 Selaawi - Laras Amelia Maharani; Yeni Cania Puspita (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2024)
This research is motivated by the low ability to read news text comprehension and a lack of understanding of reading strategies. The purpose of this research is to test the ability to learn to read and understand news texts using the ECOLA (Extending Concepts through Language Activities) technique. The research method used was a quasi-experimental quantitative method involving two groups of students, namely the experimental group that received learning using the ECOLA technique and the control group that received conventional learning. Data was collected through a pretest and posttest which measured the ability to read comprehension of news texts. Data analysis was performed using a difference test between the two groups. The results showed that the group that received learning using the ECOLA technique experienced a significant increase in the ability to read and understand news texts compared to the control group. Based on these findings, it shows that there is a significant difference between the experimental class and the control class as evidenced by the Kruskall Wallis test in addition to assessing student learning outcomes by calculating the average. Then, it can be an effective approach in improving students' reading comprehension skills of news texts as evidenced by the control class gain of 0.4602. While the value of the difference (gain) for the experimental class using the ECOLA technique is 0.6550 . The implication of this study is the importance of applying the ECOLA technique in teaching reading comprehension of news texts to improve students' competence in understanding and interpreting the information contained in news texts..